The Structure of the Near-Surface Layer of the AAAC Overhead Power Line Wires after Operation and Its Effect on Their Elastic, Microplastic, and Electroresistance Properties - Maria V. Narykova; Aleksandr A. Levin; Nikita D. Prasolov; Alexey I. Lihachev; Boris K. Kardashev; Andrej G. Kadomtsev; Andrei G. Panfilov; Roman V. Sokolov; Pavel N. Brunkov; Makhsud M. Sultanov; Vasily N. Kuryanov; Vladimir N. Tyshkevich (Crystals, 2022)
Overhead power-transmission lines are one of the most important components of modern infrastructure. Their service life is determined by the state of the near-surface defect layers (NSDLs) of wires constituting these lines. Both the structure and microstructure of the NSDLs of wires of the AAAC type (All Aluminum Alloy Conductor), which were in operation during 0 (new) to 62 years, were investigated by methods of the X-ray (XRD) and electron back-scattering diffraction, optical microscopy, and resistivity measurements, as well as by means of densitometric and acoustic measurements with layer-by-layer removal of the near-surface material by etching. Two characteristic thicknesses of the NSDLs were obtained, different methods providing close results, namely, ~30–50 μm and ~56–140 μm. According to the mass-density distribution (XRD), these characteristic thicknesses correspond to the depths from the surface where they occur, respectively, ~70% and ~99% of the density drop in comparison with the bulk density value. The rate of increase in NSDL thickness is ~4 μm/year in the interval from 0 to 18 years. Results of investigation of elastic and microplastic properties of wires after removal of ~35 μm of the upper layer are also presented.